Engineering electromagnetics : applications - Bansal, Rajeev (Boca Raton, Florida : CRC Press, 2006)
Electromagnetics is important in too many fields for knowledge to be gathered on the fly. Providing an understanding of Electromagnetics, this book demonstrates how to apply the underlying physical concepts within the particular context of the problem. It covers topics like radar, wireless, satellite, and optical communication technologies.
Front Cover; Preface; Contents; Acknowledgments; Editor; Contributors; 1. Radar; 2. Wireless Communication Systems; 3. Satellite Communication Systems; 4. Optical Communications; 5. Numerical Techniques; 6. Biological Effects of Electromagnetic Fields; 7. Biomedical Applications of Electromagnetic Engineering; 8. Measurement Techniques for the Electromagnetic Characterization of Biological Materials; Appendix A; Appendix B; Appendix C; Index.
Includes bibliographical references and index.
Keywords: ELECTROMAGNETISM